OPTIMIZING TASK EXECUTION OF THE SECURITY AND SAFETY UNIT ON KLATEN POLICE TRAFFIC UNIT TO PREVENT MOTORCYCLES ACCIDENT ON JOGJA-SOLO HIGHWAY IN ORDER TO REALIZE SECURITY SAFETY ORDERLY AND SMOOTH TRAFFIC - ALBERTUS BAGAS SATRIA ALBERTUS BAGAS SATRIA (Indonesian Journal of Police Studies, 2022)
ABSTRACT OPTIMIZING TASK EXECUTION OF THE SECURITY AND SAFETY UNIT ON KLATEN POLICE TRAFFIC UNIT TO PREVENT MOTORCYCLES ACCIDENT ON JOGJA-SOLO HIGHWAY IN ORDER TO REALIZE SECURITY SAFETY ORDERLY AND SMOOTH TRAFFIC ALBERTUS BAGAS SATRIA, 18.124, albertussatriasmatn@gmail.com Indonesia is the fourth largest country in populations, with the total population of 270,20 million people in 2020. The population grows significantly 32,56 million people in the last 10 years. The population increases throughout the years is also affected the use of motorcycles the total amount of motorcycles that are not followed with adequate facilities of traffic signs makes the motorcycles accident cases raising throughout the years, based on the traffic accident data from klaten police traffic unit it is stated that the amount of accident cases in Klaten Regency from 2018-2021 is increases by 24% and motorcycles is being the most popular cases that makes traffic accident by 2018-2021 periods. The accident mostly happen in Jogja-Solo highway, there are 11 high risk locations for accident and eight within that is happened in Jogja-Solo highway. Within the data it is important to have a research about further research about accident data, contributing factors to the accident and solutions to optimalize the role of security and safety unit in Klaten police station to prevent accident cases of motorcycles in Jogja-Solo highway. Furthermore, problem solving was carried out by applying management theory by George R.Terry through elements of planning, organizing, actuating, controlling and SWOT analysis theory by Fajar Nur’Aeni which deepened through the SWOT matrixs approach. After that the concept of security and safety unit, social traffic education, kamseltibcar lantas, traffic accidents are also applied as an analytical tool in formulating and finding the right solution for the problems. With the data obtained and associated with the theories and concepts used as the analytical knife above, several conclusions and suggestions were found regarding the role of the Klaten Police traffic security and safety unit and the efforts made to optimalize the Klaten Police traffic security and safety unit to prevent motorcycles accident on the Jogja-Solo highway in order to realize kamseltibcar lantas.